Overview and quality assurance for the oral health component of the National Health and Nutrition Examination Survey (NHANES), 2011–2014 - Bruce A. Dye (BMC Oral Health, 2019)
Abstract Background Following implementation in 2009–2010 to the oral health component for the National Health and Nutrition Examination Survey (NHANES), a full-mouth periodontal examination was continued during 2011–2014. Additionally, a comprehensive dental caries assessment was re-introduced in 2011 after a 6-year absence from NHANES. This report provides oral health content information and results of dental examiner reliability statistics for key intraoral assessments conducted by dentists during 2011–2014. Methods During the 2011–2014 NHANES 17,463 persons age 1 and older representing the US civilian, non-institutionalized population received an oral health examination. From this group, 387 individuals underwent a repeat examination conducted by the survey reference examiner. A combination of examiner training and calibration, electronic data capture, and ongoing performance evaluation with statistical monitoring was used to ensure conformance with NHANES protocols and data comparability to prior data collection periods. Results During 2011–2014, the Kappa statistics for the tooth count assessment ranged from 0.96 to 1.00, for untreated dental caries Kappa scores were 0.93 to 1.00. The overall Kappa statistics for identifying combined moderate-severe periodontitis using the CDC/AAP case definition was 0.66 and 0.69 with percent agreement of 83 to 85% during 2011–2014. When evaluating inter-examiner agreement using information collected from 3 periodontal sites for comparability to the NHANES 2003–04 periodontal examination protocols, Kappa scores for combined moderate-severe periodontitis was 0.65 and 0.80 during 2011–2014. For total mean attachment loss and pocket depth across all 6 periodontal sites, the inter-class coefficients (ICCs) ranged from 0.80–0.90 and 0.79–0.86 respectively. Site-specific mean attachment loss ICCs were generally higher for the 4 interproximal measurements compared to the 2 mid-site probing measurements and this observation was similar in 2009–2010. Conclusion During 2011–2014, results overall indicate a high level of data quality and substantial examiner reliability for tooth count and dentition; reliability for periodontal disease, across various assessments, was at least moderate. When comparing the 2011–2014 examiner performance to findings from 2003 to 2004, comparable concordance between the examiners and the reference examiner exists.